Pengaruh Promosi Media Instagram, Lifestyle dan Brand Image Terhadap Keputusan Pembelian Pada Kopi Kenangan Suhat Kota Malang (Studi Kasus Mahasiswa di Kota Malang) - Dimas Aditya Pratama; Agus Widarko; Muhammad Tody Arsyianto (UNIVERSITAS ISLAM MALANG, 2026)
Abstract The dynamic of contemporary developments have driven the coffee shop industry in Indonesia to experience rapid growth. This study examines the influence of instagram based promotional activities, lifestyle and brand image on consumer purchasing decisions. The population consist of university student in Malang City with a sample of 100 respondent determined using the slovin formula and selected through a purposive sampling method. A quantitative approach was employed, while data processing and analysis were conducted using SPSS version 27. The analytical procedures included validity and reliability testing, normality test, classical assumtion test, hypothesis test, multiple linear regression analysis and calculation of the coefficient of determination (Adjusted R2). Result indicate instagram promotion, lifestyle and brand image plays an important role in shaping purchasing decision, both simultaneously and partially.. Keywords: Instagram Media Promotion, Lifestyle, Brand Image, Purchasing Decisions